Frequent weak seismic shakings affect landslide occurrence and threaten 20% of Nepal’s population - Fang Chen; Bo Yu; Huadong Guo; Pascal Lacroix; Noélie Bontemps; Shengwen Qi; Umesh K. Haritashya; Jeffrey S. Kargel; Ni Huang; Lei Wang (Science Bulletin, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

The i-FSC proxy for predicting inter-event and spatial variation of topographic site effects - Aline Bou Nassif; Emeline Maufroy; Pascal Lacroix; Emmanuel Chaljub; Mathieu Causse; Pierre-Yves Bard (Bulletin of Earthquake Engineering, 2025)
Our study focuses on predicting topographic amplification of ground motion in the near-source region, where seismic rays reach the free-surface at varying incidence angles. We rely on data from previous 3D numerical simulations conducted on a topographic relief with a homogeneous medium. First, using neural networks, we identify which key parameters, describing the geometric characteristics of the relief relative to the seismic source position, control ground motion amplification. Then, we determine the functional form that relates these parameters to the simulated amplifications. Subsequently, we conduct a regression study to develop a model of topographic amplification, referred to as the i-FSC proxy (Illuminated Frequency-Scaled Curvature). Our estimator depends on the frequency-scaled (1) curvature, a parameter that accounts for the occurrence of amplifications over convex topographies and de-amplification over concave ones; (2) normalized illumination angle, a newly defined parameter that quantifies the slope exposure to the incoming wavefield, accounting for high amplification on slopes oriented opposite to the seismic source. The illumination parameter reduces the uncertainties of the proxy by a factor of 2 compared to estimators that rely solely on curvature. The proxy does not require high computational resources. It uses a digital elevation map and a seismic source position to predict amplification factors (without lithological effects) for an S -wave at any site on the surface topography. It allows exploration of variations in topographic amplification near seismic sources, representing a significant breakthrough as areas closest to the fault typically sustain the highest damages. A MATLAB script performing the i-FSC calculations is provided.

Estimating urban seismic damages and debris from building-level simulations: application to the city of Beirut, Lebanon - Rouba Iskandar; Bilal Al Tfaily; Cécile Cornou; Pierre-Yves Bard; Bertrand Guillier; Jacques Harb; Pascal Lacroix; Jocelyne Adjizian-Gérard; Elise Beck; Julie Dugdale; Christelle Salameh; Nada Saliba; et al. (Bulletin of Earthquake Engineering, 2023)

Cumulative and potential synergistic effects of seven different bisphenols on human granulosa cells in vitro? - Marie-Emilie Lebachelier de la Riviere; Luyao Wu; Manon Gayet; Marie Bousquet; Charlotte Buron; Claire Vignault; Ophélie Téteau; Alice Desmarchais; Virginie Maillard; Svetlana Uzbekova; Fabrice Guérif; Marlène Lacroix; et al. (Environmental Pollution, 2023)

Landslides induced by the 2017 Mw7.3 Sarpol Zahab earthquake (Iran) - Aya Cheaib; Pascal Lacroix; Swann Zerathe; Denis Jongmans; Najmeh Ajorlou; Marie-Pierre Doin; James Hollingsworth; Chadi Abdallah (Landslides, 2022)

Multi-method investigation of mass transfer mechanisms in a retrogressive clayey landslide (Harmalière, French Alps) - Sylvain Fiolleau; Denis Jongmans; Gregory Bièvre; Guillaume Chambon; Pascal Lacroix; Agnès Helmstetter; Marc Wathelet; Michel Demierre (Landslides, 2021)

Development and implementation of eco-genomic tools for aquatic ecosystem biomonitoring: the SYNAQUA French-Swiss program - Estelle Lefrançois; Laure Apothéloz-Perret-Gentil; Philippe Blancher; Samuel Botreau; Cécile Chardon; Laura Crepin; Tristan Cordier; Arielle Cordonier; Isabelle Domaizon; Benoit J. D. Ferrari; Julie Guéguen; Jean-Christophe Hustache; et al. (Environmental Science and Pollution Research, 2018)

Regulatory role of UvrY in adaptation of Photorhabdus luminescens growth inside the insect - Evelyne Krin; Sylviane Derzelle; Karine Bedard; Minou Adib‐Conquy; Evelyne Turlin; Pascal Lenormand; Marie‐Francoise Hullo; Isabelle Bonne; Nesrine Chakroun; Celine Lacroix; Antoine Danchin (Environmental Microbiology, 2008)
Summary We report global expression profiling of a uvrY‐ deficient mutant of Photorhabdus luminescens . We found that the regulator moiety of the two‐component regulatory system BarA/UvrY regulated more than 500 target genes coding for functions involved in the synthesis of major compartments and metabolic pathways of the cell. This regulation appeared to be in part indirect as UvrY affected the expression of several regulators. Indeed, the flagellum biosynthesis transcription activator FlhC and the flagella regulon were induced in the absence of UvrY, leading to a hyperflagellated phenotype and an increase in motility and biofilm formation. Two major regulatory systems were also altered: the type 2 quorum‐sensing inducer AI‐2 was activated by UvrY, and the CsrA regulator function appeared to be repressed by the increase of the small‐untranslated RNA csrB , the CsrA activity inhibitor TldD and the chaperonin GroESL. Both through and independently of these systems, UvrY regulated oxidative stress resistance; bioluminescence; iron, sugar and peptide transport; proteases; polyketide synthesis enzymes and nucleobases recycling, related to insect degradation and assimilation by bacteria. As a consequence, the uvrY ‐deficient strain exhibited a decreased killing of insect cells and a reduced growth on insect cells culture, suggesting a UvrY role in the adaptation of P. luminescens inside the insect.